HUBUNGAN ANTARA PENGATURAN DIRI DENGAN ASPIRASI KARIR PADA SISWA KELAS 1 SD - Elisa dan Arundati Shinta (Jurnal Psikologi, 2014)
Objective of this research is to verify the relationship between career aspiration and self-regulation among first grade children. Gender stereotype career aspiration is more likely chosen by children with external self-regulation. The more internal their self-regulation, their career aspiration is more likely counter gender stereotype. Children with internal self-regulation are more certain when they have to violating the gender norm. The dependent variable of this research is children's career aspiration, and the independent variable is children's self-regulation. Two scales are utilized i.e. the Career Aspiration Scale and the Self-regulation Scale. There were 85 first grade children, aged 6-7, in urban areas participated in this research. This research revealed that there is no relationship between career aspiration and selfregulation on children (F(l,74)= 0.096, p<0.05). The plausible reason is that those Indonesian families are more likely collective contrast to the West families. Therefore Indonesian children are not motivated to have internal self-regulation, and therefore their career aspiration choice is more likely gender stereotype.